3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task.<br

3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Objective: Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task. Methods: 18 healthy volunteers underwent two resting state and a stimulus driven measurement using a finger tapping motor task at 3 and 7 T, respectively. The SNR for each field strength was adjusted by targeted voxel size variation to minimize the effect of SNR on the field strength specific outcome. Spatial and temporal characteristics of resting state ICA, network graphs, and motor task related activated areas were compared. Finally, a graph theoretical approach was used to detect resting state modulation subsequent to a simple motor task. Results: Spatial extensions of resting state ICA and motor task related activated areas were consistent between field strengths, but temporal characteristics varied, indicating that 7 T achieved a higher functional specificity of the BOLD response than 3 T-fMRI. Following the motor task, only 7 T-fMRI enabled the detection of highly specific connectivity modulations representing an “offline replay” of previous motor activation. Modulated connections of the motor cortex were directly linked to brain regions associated with memory consolidation. Conclusion: These findings reveal how memory processing is initiated even after simple motor tasks, and that it begins earlier than previously shown. Thus, the superior capability of 7 T-fMRI to detect subtle functional dynamics promises to improve diagnostics and therapeutic assessment of neurological diseases.
CRIS-Team Scopus Importer:2023-09-08
Keywords: 7T fMRI; graph theory; memory; motor task; offline replay; resting state

Adult alcohol drinking and emotional tone are mediated by neutral sphingomyelinase during development in males - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Cerebral Cortex, 2022)
Alcohol use, abuse, and addiction, and resulting health hazards are highly sex-dependent with unknown mechanisms. Previously, strong links between the SMPD3 gene and its coded protein neutral sphingomyelinase 2 (NSM) and alcohol abuse, emotional behavior, and bone defects were discovered and multiple mechanisms were identified for females. Here we report strong sex-dimorphisms for central, but not for peripheral mechanisms of NSM action in mouse models. Reduced NSM activity resulted in enhanced alcohol consumption in males, but delayed conditioned rewarding effects. It enhanced the acute dopamine response to alcohol, but decreased monoaminergic systems adaptations to chronic alcohol. Reduced NSM activity increased depression- and anxiety-like behavior, but was not involved in alcohol use for the self-management of the emotional state. Constitutively reduced NSM activity impaired structural development in the brain and enhanced lipidomic sensitivity to chronic alcohol. While the central effects were mostly opposite to NSM function in females, similar roles in bone-mediated osteocalcin release and its effects on alcohol drinking and emotional behavior were observed. These findings support the view that the NSM and multiple downstream mechanism may be a source of the sex-differences in alcohol use and emotional behavior.
CRIS-Team WoS Importer:2022-04-15
Keywords: neutral sphingomyelinase; osteocalcin; depression; alcohol; anxiety

A New Analysis of Resting State Connectivity and Graph Theory Reveals Distinctive Short-Term Modulations due to Whisker Stimulation in Rats - Kreitz, Silke; De Celis Alonso, Benito; Uder, Michael; Heß, Andreas (Frontiers in Neuroscience, 2018)
Resting state (RS) connectivity has been increasingly studied in healthy and diseased brains in humans and animals. This paper presents a new method to analyze RS data from fMRI that combines multiple seed correlation analysis with graph-theory (MSRA). We characterize and evaluate this new method in relation to two other graph-theoretical methods and ICA. The graph-theoretical methods calculate cross-correlations of regional average time-courses, one using seed regions of the same size (SRCC) and the other using whole brain structure regions (RCCA). We evaluated the reproducibility, power, and capacity of these methods to characterize short-term RS modulation to unilateral physiological whisker stimulation in rats. Graph-theoretical networks found with the MSRA approach were highly reproducible, and their communities showed large overlaps with ICA components. Additionally, MSRA was the only one of all tested methods that had the power to detect significant RS modulations induced by whisker stimulation that are controlled by family-wise error rate (FWE). Compared to the reduced resting state network connectivity during task performance, these modulations implied decreased connectivity strength in the bilateral sensorimotor and entorhinal cortex. Additionally, the contralateral ventromedial thalamus (part of the barrel field related lemniscal pathway) and the hypothalamus showed reduced connectivity. Enhanced connectivity was observed in the amygdala, especially the contralateral basolateral amygdala (involved in emotional learning processes). In conclusion, MSRA is a powerful analytical approach that can reliably detect tiny modulations of RS connectivity. It shows a great promise as a method for studying RS dynamics in healthy and pathological conditions.
EVALuna2:34696

Association of brain functional magnetic resonance activity with response to tumor necrosis factor inhibition in rheumatoid arthritis - Rech, Jürgen; Heß, Andreas; Finzel, Stephanie; Kreitz, Silke; Sergeeva, Marina; Englbrecht, Matthias; Dörfler, Arnd; Saake, Marc; Schett, Georg (Arthritis and Rheumatism, 2013)
Objective To test whether brain activity predicts the response to tumor necrosis factor inhibitors (TNFi) in patients with rheumatoid arthritis (RA). Since clinical and laboratory parameters have proven unsuccessful in predicting response, we followed a radically different concept, hypothesizing that response to TNFi depends on central nervous system activity rather than the clinical signs of disease. Methods Sequential testing by functional magnetic resonance imaging (MRI) of the brain, anatomic MRI of the hand, and clinical assessment of arthritis were carried out in 10 patients with active RA before and 3, 7, and 28 days after the start of TNFi treatment. Results Baseline demographic and disease-specific parameters were identical in TNFi responders and nonresponders. The mean ± SEM decrease in the Disease Activity Score in 28 joints after 28 days was -1.8 ± 0.3 in TNFi responders (n = 5) and -0.2 ± 0.1 in nonresponders (n = 5). Responders showed significantly higher baseline activation in thalamic, limbic, and associative areas of the brain than nonresponders. Moreover, brain activity decreased within 3 days after TNFi exposure in the responders, preceding clinical responses (day 7) and responses observed on the anatomic hand MRI (day 28). Conclusion These data suggest that response to TNFi depends on brain activity in RA patients, reflecting the subjective perception of disease. Copyright © 2013 by the American College of Rheumatology.
CRIS-Team Scopus Importer:2021-02-03

Blockade of TNF-α rapidly inhibits pain responses in the central nervous system - Heß, Andreas; Axmann, Roland; Rech, Jürgen; Finzel, Stephanie; Heindl-Erdmann, Cornelia; Kreitz, Silke; Sergeeva, Marina; Saake, Marc; Garcia, Meritxell; Kollias, George; Straub, Rainer H.; Sporns, Olaf; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
There has been a consistent gap in understanding how TNF-α neutralization affects the disease state of arthritis patients so rapidly, considering that joint inflammation in rheumatoid arthritis is a chronic condition with structural changes. We thus hypothesized that neutralization of TNF-α acts through the CNS before directly affecting joint inflammation. Through use of functional MRI (fMRI), we demonstrate that within 24 h after neutralization of TNF-α, nociceptive CNS activity in the thalamus and somatosensoric cortex, but also the activation of the limbic system, is blocked. Brain areas showing blood-oxygen level-dependent signals, a validated method to assess neuronal activity elicited by pain, were significantly reduced as early as 24 h after an infusion of a monoclonal antibody to TNF-α. In contrast, clinical and laboratory markers of inflammation, such as joint swelling and acute phase reactants, were not affected by anti-TNF-α at these early time points. Moreover, arthritic mice overexpressing human TNF-α showed an altered pain behavior and amore intensive, widespread, and prolonged brain activity upon nociceptive stimuli compared with wild-type mice. Similar to humans, these changes, as well as the rewiring of CNS activity resulting in tight clustering in the thalamus, were rapidly reversed after neutralization of TNF-α. These results suggest that neutralization of TNF-α affects nociceptive brain activity in the context of arthritis, long before it achieves antiinflammatory effects in the joints.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Antiinflammatory therapy; Cytokines

Central amygdala circuit dynamics underlying the benzodiazepine anxiolytic effect - Griessner, Johannes; Pasieka, Manuel; Böhm, Vincent; Grössl, Florian; Kaczanowska, Joanna; Pliota, Pinelopi; Kargl, Dominic; Werner, Barbara; Kaouane, Nadia; Strobelt, Sandra; Kreitz, Silke; Heß, Andreas; et al. (Molecular Psychiatry, 2021)
Benzodiazepines (BZDs) have been a standard treatment for anxiety disorders for decades, but the neuronal circuit interactions mediating their anxiolytic effect remain largely unknown. Here, we find that systemic BZDs modulate central amygdala (CEA) microcircuit activity to gate amygdala output. Combining connectome data with immediate early gene (IEG) activation maps, we identified the CEA as a primary site for diazepam (DZP) anxiolytic action. Deep brain calcium imaging revealed that brain-wide DZP interactions shifted neuronal activity in CEA microcircuits. Chemogenetic silencing showed that PKCδ+/SST− neurons in the lateral CEA (CEAl) are necessary and sufficient to induce the DZP anxiolytic effect. We propose that BZDs block the relay of aversive signals through the CEA, in part by local binding to CEAl SST+/PKCδ− neurons and reshaping intra-CEA circuit dynamics. This work delineates a strategy to identify biomedically relevant circuit interactions of clinical drugs and highlights the critical role for CEA circuitry in the pathophysiology of anxiety.
CRIS-Team Scopus Importer:2021-02-12

Central amygdala circuitry modulates nociceptive processing through differential hierarchical interaction with affective network dynamics - Wank, Isabel; Pliota, Pinelopi; Badurek, Sylvia; Kraitsy, Klaus; Kaczanowska, Joanna; Griessner, Johannes; Kreitz, Silke; Heß, Andreas; Haubensak, Wulf (Communications Biology, 2021)
The central amygdala (CE) emerges as a critical node for affective processing. However, how CE local circuitry interacts with brain wide affective states is yet uncharted. Using basic nociception as proxy, we find that gene expression suggests diverging roles of the two major CE neuronal populations, protein kinase C δ-expressing (PKCδ+) and somatostatin-expressing (SST+) cells. Optogenetic (o)fMRI demonstrates that PKCδ+/SST+ circuits engage specific separable functional subnetworks to modulate global brain dynamics by a differential bottom-up vs. top-down hierarchical mesoscale mechanism. This diverging modulation impacts on nocifensive behavior and may underly CE control of affective processing.
CRIS-Team Scopus Importer:2021-06-25

Combined resting state-fMRI and calcium recordings show stable brain states for task-induced fMRI in mice under combined ISO/MED anesthesia - Pradier, Bruno; Wachsmuth, Lydia; Nagelmann, Nina; Segelcke, Daniel; Kreitz, Silke; Heß, Andreas; Pogatzki-Zahn, Esther M.; Faber, Cornelius (NeuroImage, 2021)
For fMRI in animal models, the combination of low-dose anesthetic, isoflurane (ISO), and the sedative medetomidine (MED) has recently become an advocated regimen to achieve stable neuronal states and brain networks in rats that are required for reliable task-induced BOLD fMRI. However, in mice the temporal stability of neuronal states and networks in resting-state (rs)-fMRI experiments during the combined ISO/MED regimen has not been systematically investigated. Using a multimodal approach with optical calcium (Ca2+) recordings and rs-fMRI, we investigated cortical neuronal/astrocytic Ca2+activity states and brain networks at multiple time points while switching from anesthesia with 1% ISO to a combined ISO/MED regimen. We found that cortical activity states reached a steady-state 45 min following start of MED infusion as indicated by stable Ca2+ transients. Similarly, rs-networks were not statistically different between anesthesia with ISO and the combined ISO/MED regimen 45 and 100 min after start of MED. Importantly, during the transition time we identified changed rs-network signatures that likely reflect the different mode of action of the respective anesthetic; these included a dose-dependent increase in cortico-cortical functional connectivity (FC) presumably caused by reduction of ISO concentration and decreased FC in subcortical arousal nuclei due to MED infusion. Furthermore, we report detection of visual stimulation-induced BOLD fMRI during the stable ISO/MED neuronal state 45 min after induction. Based on our findings, we recommend a 45-minute waiting period after switching from ISO anesthesia to the combined ISO/MED regimen before performing rs- or task-induced fMRI experiments.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Anesthesia; Brain state; Graph theory; Mouse; Resting-state fMRI; Task-induced fMRI

Common functional networks in the mouse brain revealed by multi-centre resting-state fMRI analysis - Grandjean, Joanes; Canella, Carola; Anckaerts, Cynthia; Ayrancı, Gülebru; Bougacha, Salma; Bienert, Thomas; Buehlmann, David; Coletta, Ludovico; Gallino, Daniel; Gass, Natalia; Garin, Clément M.; Nadkarni, Nachiket Abhay; et al. (NeuroImage, 2020)
Preclinical applications of resting-state functional magnetic resonance imaging (rsfMRI) offer the possibility to non-invasively probe whole-brain network dynamics and to investigate the determinants of altered network signatures observed in human studies. Mouse rsfMRI has been increasingly adopted by numerous laboratories worldwide. Here we describe a multi-centre comparison of 17 mouse rsfMRI datasets via a common image processing and analysis pipeline. Despite prominent cross-laboratory differences in equipment and imaging procedures, we report the reproducible identification of several large-scale resting-state networks (RSN), including a mouse default-mode network, in the majority of datasets. A combination of factors was associated with enhanced reproducibility in functional connectivity parameter estimation, including animal handling procedures and equipment performance. RSN spatial specificity was enhanced in datasets acquired at higher field strength, with cryoprobes, in ventilated animals, and under medetomidine-isoflurane combination sedation. Our work describes a set of representative RSNs in the mouse brain and highlights key experimental parameters that can critically guide the design and analysis of future rodent rsfMRI investigations.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Connectome; Default-mode network; Functional connectivity; ICA; Seed-based

Comparing brain activity patterns during spontaneous exploratory and cue-instructed learning using single photon-emission computed tomography (SPECT) imaging of regional cerebral blood flow in freely behaving rats - Mannewitz, A.; Bock, J.; Kreitz, Silke; Heß, Andreas; Goldschmidt, J.; Scheich, H.; Braun, Katharina (Brain Structure & Function, 2018)
Learning can be categorized into cue-instructed and spontaneous learning types; however, so far, there is no detailed comparative analysis of specific brain pathways involved in these learning types. The aim of this study was to compare brain activity patterns during these learning tasks using the in vivo imaging technique of single photon-emission computed tomography (SPECT) of regional cerebral blood flow (rCBF). During spontaneous exploratory learning, higher levels of rCBF compared to cue-instructed learning were observed in motor control regions, including specific subregions of the motor cortex and the striatum, as well as in regions of sensory pathways including olfactory, somatosensory, and visual modalities. In addition, elevated activity was found in limbic areas, including specific subregions of the hippocampal formation, the amygdala, and the insula. The main difference between the two learning paradigms analyzed in this study was the higher rCBF observed in prefrontal cortical regions during cue-instructed learning when compared to spontaneous learning. Higher rCBF during cue-instructed learning was also observed in the anterior insular cortex and in limbic areas, including the ectorhinal and entorhinal cortexes, subregions of the hippocampus, subnuclei of the amygdala, and the septum. Many of the rCBF changes showed hemispheric lateralization. Taken together, our study is the first to compare partly lateralized brain activity patterns during two different types of learning.
EVALuna2:214359

Distinct functional cerebral hypersensitivity networks during incisional and inflammatory pain in rats - Kreitz, Silke; Pradier, Bruno; Segelcke, Daniel; Amirmohseni, Saeedeh; Heß, Andreas; Faber, Cornelius; Pogatzki-Zahn, Esther M. (Current Research in Neurobiology, 2025)
Although the pathophysiology of pain has been investigated tremendously, there are still many open questions with regard to specific pain entities and their pain-related symptoms. To increase the translational impact of (preclinical) animal neuroimaging pain studies, the use of disease-specific pain models, as well as relevant stimulus modalities, are critical. We developed a comprehensive framework for brain network analysis combining functional magnetic resonance imaging (MRI) with graph-theory (GT) and data classification by linear discriminant analysis. This enabled us to expand our knowledge of stimulus modalities processing under incisional (INC) and pathogen-induced inflammatory (CFA) pain entities compared to acute pain conditions. GT-analysis has uncovered specific features in pain modality processing that align well with those previously identified in humans. These include areas such as S1, M1, CPu, HC, piriform, and cingulate cortex. Additionally, we have identified unique Network Signatures of Pain Hypersensitivity (NSPH) for INC and CFA. This leads to a diminished ability to differentiate between stimulus modalities in both pain models compared to control conditions, while also enhancing aversion processing and descending pain modulation. Our findings further show that different pain entities modulate sensory input through distinct NSPHs. These neuroimaging signatures are an important step toward identifying novel cerebral pain biomarkers for certain diseases and relevant outcomes to evaluate target engagement of novel therapeutic and diagnostic options, which ultimately can be translated to the clinic.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Animal neuroimaging studies; Cerebral pain biomarkers; Disease-specific pain models; Functional MRI (fMRI); Graph theory in pain analysis; Incisional pain (INC); Inflammatory pain (CFA); Linear discriminant analysis; Network signatures of pain hypersensitivity (NSPH); Pain pathophysiology

Fat/carbohydrate ratio but not energy density determines snack food intake and activates brain reward areas - Hoch, Tobias; Kreitz, Silke; Gaffling, Simone; Pischetsrieder, Monika; Heß, Andreas (Scientific Reports, 2015)
The snack food potato chips induces food intake in ad libitum fed rats, which is associated with modulation of the brain reward system and other circuits. Here, we show that food intake in satiated rats is triggered by an optimal fat/carbohydrate ratio. Like potato chips, an isocaloric fat/carbohydrate mixture influenced whole brain activity pattern of rats, affecting circuits related e.g. to reward/addiction, but the number of modulated areas and the extent of modulation was lower compared to the snack food itself.
UnivIS-Import:2015-07-08:Pub.2015.nat.dchph.llmch.fatcar

Imaging of Functional Brain Circuits during Acquisition and Memory Retrieval in an Aversive Feedback Learning Task: Single Photon Emission Computed Tomography of Regional Cerebral Blood Flow in Freely Behaving Rats - Braun, Katharina; Mannewitz, Anja; Bock, Joerg; Kreitz, Silke; Heß, Andreas; Scheich, Henning; Goldschmidt, Juergen (Brain Sciences, 2021)
Active avoidance learning is a complex form of aversive feedback learning that in humans and other animals is essential for actively coping with unpleasant, aversive, or dangerous situations. Since the functional circuits involved in two-way avoidance (TWA) learning have not yet been entirely identified, the aim of this study was to obtain an overall picture of the brain circuits that are involved in active avoidance learning. In order to obtain a longitudinal assessment of activation patterns in the brain of freely behaving rats during different stages of learning, we applied single-photon emission computed tomography (SPECT). We were able to identify distinct prefrontal cortical, sensory, and limbic circuits that were specifically recruited during the acquisition and retrieval phases of the two-way avoidance learning task.
CRIS-Team WoS Importer:2021-06-04

Imaging the influence of peripheral TRPV1-signaling on cerebral nociceptive processing applying fMRI-based graph theory in a resiniferatoxin rat model - Wank, Isabel; Kutsche, Lisa; Kreitz, Silke; Reeh, Peter; Heß, Andreas (PLoS ONE, 2022)
Resiniferatoxin (RTX), an extract from the spurge plant Euphorbia resinifera, is a potent agonist of the transient receptor potential cation channel subfamily V member 1 (TRPV1), mainly expressed on peripheral nociceptors—a prerequisite for nociceptive heat perception. Systemic overdosing of RTX can be used to desensitize specifically TRPV1-expressing neurons, and was therefore utilized here to selectively characterize the influence of TRPV1-signaling on central nervous system (CNS) temperature processing. Resting state and CNS temperature processing of male rats were assessed via functional magnetic resonance imaging before and after RTX injection. General linear model-based and graph-theoretical network analyses disentangled the underlying distinct CNS circuitries. At baseline, rats displayed an increase of nociception-related response amplitude and activated brain volume that correlated highly with increasing stimulation temperatures. In contrast, RTX-treated rats showed a clear disruption of thermal nociception, reflected in a missing increase of CNS responses to temperatures above 48°C. Graph-theoretical analyses revealed two distinct brain subnetworks affected by RTX: one subcortical (brainstem, lateral and medial thalamus, hippocampus, basal ganglia and amygdala), and one cortical (primary sensory, motor and association cortices). Resting state analysis revealed first, that peripheral desensitization of TRPV1-expressing neurons did not disrupt the basic resting-state-network of the brain. Second, only at baseline, but not after RTX, noxious stimulation modulated the RS-network in regions associated with memory formation (e.g. hippocampus). Altogether, the combination of whole-brain functional magnetic resonance imaging and RTX-mediated desensitization of TRPV1-signaling provided further detailed insight into cerebral processing of noxious temperatures.
CRIS-Team Scopus Importer:2022-05-20

Impaired maturation of resting-state connectivity in anorexia nervosa from adolescence to adulthood: differential mechanisms of consummatory vs. anticipatory responses through a symptom provocation paradigm - Mendez Torrijos, Andrea; Selvakumar, Mageshwar; Kreitz, Silke; Rösch, Julie; Dörfler, Arnd; Paslakis, Georgios; Krehbiel, Johannes; Steins-Löber, Sabine; Kratz, Oliver; Horndasch, Stefanie; Heß, Andreas (Frontiers in Behavioral Neuroscience, 2024)
This functional magnetic resonance imaging (fMRI) study examined resting-state (RS) connectivity in adolescent and adult patients with anorexia nervosa (AN) using symptom provocation paradigms. Differential food reward mechanisms were investigated through separate assessments of responses to food images and low-caloric/high-caloric food consumption. Thirteen young (≤ 21 years) and seventeen adult (> 21 years) patients with AN and age-matched controls underwent two stimulus-driven fMRI sessions involving RS scans before and after the presentation of food-related stimuli and food consumption. Graph theory and machine learning were used for analyzing the fMRI and clinical data. Healthy controls (HCs) showed widespread developmental changes, while young participants with AN exhibited cerebellum differences for high-calorie food. Young individuals with AN displayed increased connectivity during the consumption of potato chips compared to zucchini, with no differences in adults with AN. Multiparametric machine learning accurately distinguished young individuals with AN from healthy controls based on RS connectivity following food visual stimulation (“anticipatory”) and consumption (“consummatory”). This study highlights the differential food reward mechanisms and minimal developmental changes in RS connectivity from youth to adulthood in individuals with AN compared to healthy controls. Young individuals with AN demonstrated heightened reactivity to high-caloric foods, while adults showed decreased responsiveness, potentially due to desensitization. These findings shed light on aberrant eating behaviors in individuals with AN and contribute to our understanding of the chronicity of the disease.
CRIS-Team Scopus Importer:2024-11-22
Keywords: anorexia nervosa; brain development; fMRI; food intake; graph-theory; machine learning; snack food

Manganese-Enhanced Magnetic Resonance Imaging for Mapping of Whole Brain Activity Patterns Associated with the Intake of Snack Food in Ad Libitum Fed Rats - Hoch, Tobias; Kreitz, Silke; Gaffling, Simone; Pischetsrieder, Monika; Heß, Andreas (PLoS ONE, 2013)
Non-homeostatic hyperphagia, which is a major contributor to obesity-related hyperalimentation, is associated with the diet's molecular composition influencing, for example, the energy content. Thus, specific food items such as snack food may induce food intake independent from the state of satiety. To elucidate mechanisms how snack food may induce non-homeostatic food intake, it was tested if manganese-enhanced magnetic resonance imaging (MEMRI) was suitable for mapping the whole brain activity related to standard and snack food intake under normal behavioral situation. Application of the MnCl2 solution by osmotic pumps ensured that food intake was not significantly affected by the treatment. After z-score normalization and a non-affine three-dimensional registration to a rat brain atlas, significantly different grey values of 80 predefined brain structures were recorded in ad libitum fed rats after the intake of potato chips compared to standard chow at the group level. Ten of these areas had previously been connected to food intake, in particular to hyperphagia (e.g. dorsomedial hypothalamus or the anterior paraventricular thalamic nucleus) or to the satiety system (e.g. arcuate hypothalamic nucleus or solitary tract); 27 areas were related to reward/addiction including the core and shell of the nucleus accumbens, the ventral pallidum and the ventral striatum (caudate and putamen). Eleven areas associated to sleep displayed significantly reduced Mn2+-accumulation and six areas related to locomotor activity showed significantly increased Mn2+-accumulation after the intake of potato chips. The latter changes were associated with an observed significantly higher locomotor activity. Osmotic pump-assisted MEMRI proved to be a promising technique for functional mapping of whole brain activity patterns associated to nutritional intake under normal behavior.

Maternal immune activation during pregnancy impacts on brain structure and function in the adult offspring - Kreitz, Silke; Zambon, Alice; Ronovsky, Marianne; Budinsky, Lubos; Helbich, Thomas H.; Sideromenos, Spyros; Ivan, Claudiu-Ionut; Konerth, Laura; Wank, Isabel; Berger, Angelika; Pollak, Arnold; Heß, Andreas; et al. (Brain Behavior and Immunity, 2020)
Gestational infection constitutes a risk factor for the occurrence of psychiatric disorders in the offspring. Activation of the maternal immune system (MIA) with subsequent impact on the development of the fetal brain is considered to form the neurobiological basis for aberrant neural wiring and the psychiatric manifestations later in offspring life. The examination of validated animal models constitutes a premier resource for the investigation of the neural underpinnings.
CRIS-Team WoS Importer:2020-01-10

Neutral sphingomyelinase controls acute and chronic alcohol effects on brain activity - Wank, Isabel; Mittmann, Claire; Kreitz, Silke; Chestnykh, Daria; Mühle, Christiane; Kornhuber, Johannes; Ludwig, Andreas; Kalinichenko, Liubov; Müller, Christian P.; Heß, Andreas (Neuropharmacology, 2024)
Alcohol consumption is a widespread phenomenon throughout the world. However, how recreational alcohol use evolves into alcohol use disorder (AUD) remains poorly understood. The Smpd3 gene and its coded protein neutral sphingomyelinase (NSM) are associated with alcohol consumption in humans and alcohol-related behaviors in mice, suggesting a potential role in this transition. Using multiparametric magnetic resonance imaging, we characterized the role of NSM in acute and chronic effects of alcohol on brain anatomy and function in female mice. Chronic voluntary alcohol consumption (16 vol% for at least 6 days) affected brain anatomy in WT mice, reducing regional structure volume predominantly in cortical regions. Attenuated NSM activity prevented these anatomical changes. Functional MRI linked these anatomical adaptations to functional changes: Chronic alcohol consumption in mice significantly modulated resting state functional connectivity (RS FC) in response to an acute ethanol challenge (i.p. bolus of 2 g kg−1) in heterozygous NSM knockout (Fro), but not in WT mice. Acute ethanol administration in alcohol-naïve WT mice significantly decreased RS FC in cortical and brainstem regions, a key finding that was amplified in Fro mice. Regarding direct pharmacological effects, acute ethanol administration increased the regional cerebral blood volume (rCBV) in many brain areas. Here, chronic alcohol consumption otherwise attenuated the acute rCBV response in WT mice but enhanced it in Fro mice. Altogether, these findings suggest a differential role for NSM in acute and chronic functional brain responses to alcohol. Therefore, targeting NSM may be useful in the prevention or treatment of AUD.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Alcohol use disorder; Anatomical MRI; fMRI; Neutral sphingomyelinase; rCBV; Resting state functional connectivity

Neutral sphingomyelinase mediates the co-morbidity trias of alcohol abuse, major depression and bone defects - Kalinichenko, Liubov; Mühle, Christiane; Jia, Tianye; Anderheiden, Felix; Datz, Maria; Eberle, Anna-Lisa; Eulenburg, Volker; Granzow, Jonas; Hofer, Martin Jürgen; Hohenschild, Julia; Huber, Sabine; Kämpf, Stefanie; et al. (Molecular Psychiatry, 2021)
Mental disorders are highly comorbid and occur together with physical diseases, which are often considered to arise from separate pathogenic pathways. We observed in alcohol-dependent patients increased serum activity of neutral sphingomyelinase. A genetic association analysis in 456,693 volunteers found associations of haplotypes of SMPD3 coding for NSM-2 (NSM) with alcohol consumption, but also with affective state, and bone mineralisation. Functional analysis in mice showed that NSM controls alcohol consumption, affective behaviour, and their interaction by regulating hippocampal volume, cortical connectivity, and monoaminergic responses. Furthermore, NSM controlled bone–brain communication by enhancing osteocalcin signalling, which can independently supress alcohol consumption and reduce depressive behaviour. Altogether, we identified a single gene source for multiple pathways originating in the brain and bone, which interlink disorders of a mental–physical co-morbidity trias of alcohol abuse—depression/anxiety—bone disorder. Targeting NSM and osteocalcin signalling may, thus, provide a new systems approach in the treatment of a mental–physical co-morbidity trias.
CRIS-Team Scopus Importer:2021-10-08

Pharmacological and resting state fMRI reveal Osteocalcin’s effects on mouse brain regions with high Gpr37 and Gpr158 expression - Freus, Natalia; Wank, Isabel; Häfele, Maximilian; Kalinichenko, Liubov; Müller, Christian P.; Strobelt, Sandra; Ludwig, Andreas; Heß, Andreas; Kreitz, Silke (Scientific Reports, 2025)
Osteocalcin (OCN) is an endocrine hormone that signals in the periphery, regulating male fertility, energy expenditure and glucose homeostasis. It can also cross the blood-brain-barrier and act on the brain via receptors GPR37 and GPR158. In the brain, OCN influences neurotransmitter synthesis of serotonin, norepinephrine, and dopamine. OCN’s function is related to cognitive and memory performance and lack of OCN is associated with anxiety and depression-like behavior in mice. We used multiparametric magnetic resonance imaging (MRI) including pharmacological MRI and resting state functional MRI, along with gene expression data for Gpr37 and Gpr158 to investigate the physiological effects of intravenously administered OCN on the wild type mouse brain. We found four core brain regions (brainstem, limbic output, association cortex, and basal ganglia) that are highly relevant in all three analytical modalities (i.e. pharmacological, resting state MRI and gene expression) and play therefore a major role in mediating OCN’s effect in the brain. This study provides the first imaging data of the physiological impact of OCN on the mouse brain, suggesting its potential role in modulating brain function and its relevance as a candidate for further investigation in anxiety, depression, and cognitive impairments.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Allen brain atlas; Depression; Functional connectivity; Mouse fMRI; Osteocalcin; rCBV

Retrosplenial Cortex Contributes to Network Changes during Seizures in the GAERS Absence Epilepsy Rat Model. - Wachsmuth, Lydia; Datunashvili, Maia; Kemper, Katharina; Albers, Franziska; Lambers, Henriette; Lüttjohann, Annika; Kreitz, Silke; Budde, Thomas; Faber, Cornelius (Cerebral Cortex Communications, 2021)
Resting state-fMRI was performed to explore brain networks in Genetic Absence Epilepsy Rats from Strasbourg and in nonepileptic controls (NEC) during monitoring of the brain state by simultaneous optical Ca2+-recordings. Graph theoretical analysis allowed for the identification of acute and chronic network changes and revealed preserved small world topology before and after seizure onset. The most prominent acute change in network organization during seizures was the segregation of cortical regions from the remaining brain. Stronger connections between thalamic with limbic regions compared with preseizure state indicated network regularization during seizures. When comparing between strains, intrathalamic connections were prominent in NEC, on local level represented by higher thalamic strengths and hub scores. Subtle differences were observed for retrosplenial cortex (RS), forming more connections beyond cortex in epileptic rats, and showing a tendency to lateralization during seizures. A potential role of RS as hub between subcortical and cortical regions in epilepsy was supported by increased numbers of parvalbumin-positive (PV+) interneurons together with enhanced inhibitory synaptic activity and neuronal excitability in pyramidal neurons. By combining multimodal fMRI data, graph theoretical methods, and electrophysiological recordings, we identified the RS as promising target for modulation of seizure activity and/or comorbidities.
EVALuna2:489249

Snack food as a modulator of human resting-state functional connectivity. - Mendez Torrijos, Andrea; Kreitz, Silke; Ivan, Claudiu-Ionut; Konerth, Laura; Rösch, Julie; Pischetsrieder, Monika; Moll, Gunther; Kratz, Oliver; Dörfler, Arnd; Horndasch, Stefanie; Hess, Andreas (Cns Spectrums, 2018)
OBJECTIVE To elucidate the mechanisms of how snack foods may induce non-homeostatic food intake, we used resting state functional magnetic resonance imaging (fMRI), as resting state networks can individually adapt to experience after short time exposures. In addition, we used graph theoretical analysis together with machine learning techniques (support vector machine) to identifying biomarkers that can categorize between high-caloric (potato chips) vs. low-caloric (zucchini) food stimulation. METHODS Seventeen healthy human subjects with body mass index (BMI) 19 to 27 underwent 2 different fMRI sessions where an initial resting state scan was acquired, followed by visual presentation of different images of potato chips and zucchini. There was then a 5-minute pause to ingest food (day 1=potato chips, day 3=zucchini), followed by a second resting state scan. fMRI data were further analyzed using graph theory analysis and support vector machine techniques. RESULTS Potato chips vs. zucchini stimulation led to significant connectivity changes. The support vector machine was able to accurately categorize the 2 types of food stimuli with 100% accuracy. Visual, auditory, and somatosensory structures, as well as thalamus, insula, and basal ganglia were found to be important for food classification. After potato chips consumption, the BMI was associated with the path length and degree in nucleus accumbens, middle temporal gyrus, and thalamus. CONCLUSION The results suggest that high vs. low caloric food stimulation in healthy individuals can induce significant changes in resting state networks. These changes can be detected using graph theory measures in conjunction with support vector machine. Additionally, we found that the BMI affects the response of the nucleus accumbens when high caloric food is consume
Keywords: Food intake; graph theory; resting state networks; RS-fMRi; snack food; support vector machine

The impact of HCN4 channels on CNS brain networks as a new target in pain development - Häfele, Maximilian; Kreitz, Silke; Ludwig, Andreas; Heß, Andreas; Wank, Isabel (Frontiers in Network Physiology, 2023)
While it is well established that the isoform 2 of the hyperpolarization-activated cyclic nucleotide-gated cation channel (HCN2) plays an important role in the development and maintenance of pain, the role of the closely related HCN4 isoform in the processing of nociceptive signals is not known. HCN4 channels are highly expressed in the thalamus, a region important for stimulus transmission and information processing. We used a brain-specific HCN4-knockout mouse line (HCN4-KO) to explore the role of HCN4 channels in acute nociceptive processing using several behavioral tests as well as a multimodal magnetic resonance imaging (MRI) approach. Functional MRI (fMRI) brain responses were measured during acute peripheral thermal stimulation complemented by resting state (RS) before and after stimulation. The data were analyzed by conventional and graph-theoretical approaches. Finally, high-resolution anatomical brain data were acquired. HCN4-KO animals showed a central thermal, but not a mechanical hypersensitivity in behavioral experiments. The open field analysis showed no significant differences in motor readouts between HCN4-KO and controls but uncovered increased anxiety in the HCN4-KO mice. Thermal stimulus-driven fMRI (s-fMRI) data revealed increased response volumes and response amplitudes for HCN4-KO, most pronounced at lower stimulation temperatures in the subcortical input, the amygdala as well as in limbic/hippocampal regions, and in the cerebellum. These findings could be cross-validated by graph-theoretical analyses. Assessment of short-term RS before and after thermal stimulation revealed that stimulation-related modulations of the functional connectivity only occurred in control animals. This was consistent with the finding that the hippocampus was found to be smaller in HCN4-KO. In summary, the deletion of HCN4 channels impacts on processing of acute nociception, which is remarkably manifested as a thermal hypersensitive phenotype. This was mediated by the key regions hypothalamus, somatosensory cortex, cerebellum and the amygdala. As consequence, HCN4-KO mice were more anxious, and their brain-wide RS functional connectivity could not be modulated by thermal nociceptive stimulation.
Created from Fastlane, Scopus look-up
Keywords: BOLD-fMRI; graphtheory; HCN4 channels; knockout mice; multi modal MRI; pain; resting state-fMRI; thermal hypersensitivity